(untitled) (Revue D’études Interculturelles De L’image, 2013)
The paper looks into recent Russian horror films, exploring how the genre conventions associated with Hollywood are transformed and upheld in Russian cinema. The paper argues that the use of space, particularly urban venues, in horror films establishes a sense of authenticity and marks otherwise derivative generic productions as uniquely Russian. The films examined are Night and Day Watch duology (2004, 2006), Trackman (2007) and Dead Daughters (2007); all are set in contemporary Moscow.